REVIEWING PUBLIC HEALTH INTERVENTIONS ON REDUCING SEDENTARY BEHAVIOR IN WORKPLACES - Sri Indra Kurnia (International Journal Labs, 2022)
Changing behavior is a complex and major challenge. Thus, identifying effective public health interventions is important to do. This review has the main objective to identify and examine the most effective and appropriate practice to reduce sedentary behavior in the occupational environment. The main hypothesis of this review is “there is a significant reduction and interruption of sitting time among office-based workers after the implementation of the interventions”. Database searching was conducted in PubMed using the following search strategy: (